COVID-19 infection rate and mortality in a local health authority in Italy: Differences between home-dwelling and residential older adults - Stefano Orlando; Carolina de Santo; Claudia Mosconi; Francesca Di Gaspare; Pelagia Chatzichristou; Leonardo Emberti Gialloreti; Fausto Ciccacci; Laura Morciano; Donatella Varrenti; Giuseppe Liotta; Leonardo Palombi (Elsevier, 2023)
Objectives: The health emergency following the COVID-19 pandemic has seen hospital structures collapse and put in crisis nursing homes and other long-term care facilities worldwide. Our study aims to analyze and comparing the data relating to the infection rate and mortality for COVID-19 in the elderly over 75 living in the long-term care facilities and in the home-dwelling population. Study design: The study adopts a retrospective cohort design and was conducted in Italy, in the Lazio region, in the area of the Local Health Authority (LHA) named "Azienda Sanitaria Locale Roma 6". Methods: Data were extracted from the COVID-19 surveillance system of the Lazio region. The primary outcome is the SARS-CoV-2 incidence rate in the period between 1st September 2020 and 31st May 2021. The secondary outcome is the mortality rate. Results: Living in a residential versus a home-dwelling setting was associated with a higher infection rate (OR 5.03, CI 4.67-5.43; p < 0.001). The mortality rate was higher for individuals living in a residential setting (19.3 %, CI 17.1%-21.7 %) than those living at home (13.0 %, CI 11.7%-14.5 %). Conclusions: These findings confirm the high mortality in Long-Term Care Facilities and provide new information on the infection rate. The containment measures adopted in the Long-Term Care Facilities during the COVID-19 pandemic, show limited correlation with reduced risk of contagion, but could have created unintended harm for the residents by increasing the social isolation and all other causes of mortality.